The transformation of central Nigeria : essays in honor of Toyin Falola - Fwatshak, Sati Umaru; Falola, Toyin (2017)
"Using the scholarship of Toyin Falola as the entry point, The Transformation of Central Nigeria covers significant historical moments in the history of Central Nigeria, a region variously described as the North Central geopolitical zone in Nigeria's official circles and as the Middle-Belt by its indigenous populations. Centrally located in Nigeria and endowed with vast mineral and agricultural resources, Central Nigeria is a mini-Nigeria, for its ethnic diversity, complicated politics and conflicts. The main achievement of this volume is the analysis of the changes since the colonial period to the present."--Back cover.
Keywords: Middle Belt[nigeria] -- Politics and government